Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Kamar Di Hotel Daima Padang - Afri Yandi Zaputra; Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
Abstract The purpose of research is to determine the effects of Promotion mix to Room Purchasing Decision in Hotel Daima Padang. This type of research is quantitative with associative causal methods. The population in this study is the guests who have stayed with the monthly average is 1.555 people. Sampling technique is non probability sampling, using purposive sampling method. Number of sample in this research amounted to 94 people. Data collection using a questionnaire based with Likert Scale that tasted for validity and reliability. The results showed that: (1) Promotion mix is in the good category with a parcentage of 57%, (2) Puchasing decisions are in the good category with a percentage of 71%, (3) The results of the study using the t test showed that the five indicators of the promotion mix (Advertising, Personal selling, Sales promotion, Public relation and Direct marketing) room purchasing dicisions as the dependent variable significantly with the value of R square of 0,239. Keywords: promotion mix, puchasing decision